Association of Serum Calcium and 24 Hours Urinary Excretion of Calcium in Patients of Preeclampsia (Bangladesh Journal of Medical Biochemistry, 2013)
Preeclampsia is a leading cause of fetal growth retardation, infant morbidity, mortality and maternal death. Several biochemical changes occur during the course of the disease, among them serum total calcium and 24 hr urinary calcium excretion rate have drawn remarkable attention. A case control study was designed to see the association of serum calcium and 24 hours urinary excretion of calcium in patients of pre- eclampsia. The study was done from July 2008 to June 2009 in the Department of Biochemistry, Dhaka Medical College, Dhaka. Total 60 subjects were selected as study population. Among them 30 were diagnosed case of preeclampsia and 30 were age- and sex-matched normal pregnant female healthy control. It was found that the mean measured serum calcium level in case group were 1.96 ±0.17 ( mean±SD ) mmol / l and that of control group were 2.34±0.12 (mean±SD) m mol/ l respectively. The mean 24 hr urinary calcium excretion level were 94.40 ±10.68mg/24 hr (mean±SD) in case group and that of control group were 154.35±66.68 (mean ±SD) mg / 24 hr respectively. The study suggests that low level of serum calcium and urinary excretion of calcium was associated with Pre-eclampsia. DOI: http://dx.doi.org/10.3329/bjmb.v3i2.13813 Bangladesh J Med Biochem 2010; 3(2): 57-60